Crystalline Silica Impairs Efferocytosis Abilities of Human and Mouse Macrophages: Implication for Silica-Associated Systemic Sclerosis - Lescoat, Alain; Ballerie, Alice; Lelong, Marie; Augagneur, Yu; Morzadec, Claudie; Jouneau, Stéphane; Jégo, Patrick; Fardel, Olivier; Vernhet, Laurent; Lecureur, Valérie (Frontiers in Immunology, 2020)
Inhalation of crystalline silica (SiO2) is a risk factor of systemic autoimmune diseases such as systemic sclerosis (SSc) and fibrotic pulmonary disorders such as silicosis. A defect of apoptotic cell clearance (i.e. efferocytosis, a key process in the resolution of inflammation) is reported in macrophages from patients with fibrotic or autoimmune diseases. However, the precise links between SiO2 exposure and efferocytosis impairment remain to be determined. Answering to this question may help to better link innate immunity and fibrosis. In this study, we first aim to determine whether SiO2 might alter efferocytosis capacities of human and mouse macrophages. We secondly explore possible mechanisms explaining efferocytosis impairment, with a specific focus on macrophage polarization and on the RhoA/ROCK pathway, a key regulator of cytoskeleton remodeling and phagocytosis. Human monocytederived macrophages (MDM) and C57BL/6J mice exposed to SiO2 and to CFSE-positive apoptotic Jurkat cells were analyzed by flow cytometry to determine their efferocytosis index (EI). The effects of ROCK inhibitors (Y27632 and Fasudil) on EI of SiO2-exposed MDM and MDM from SSc patients were evaluated in vitro. Our results demonstrated that SiO2 significantly decreased EI of human MDM in vitro and mouse alveolar macrophages in vivo. In human MDM, this SiO2-associated impairment of efferocytosis, required the expression of the membrane receptor SR-B1 and was associated with a decreased expression of M2 polarization 2 markers (CD206, CD204, CD163). F-actin staining, RhoA activation and impairment of efferocytosis, all induced by SiO2, were reversed by ROCK inhibitors. Moreover, the EI of MDM from SSc patients was similar to the EI of in vitro-SiO2-exposed MDM and Y27632 significantly increased SSc MDM efferocytosis capacities, suggesting a likewise activation of the RhoA/ROCK pathway in SSc. Altogether, our results demonstrate that SiO2 exposure may contribute to the impairment of efferocytosis capacities of mouse and human macrophages but also of MDM in SiO2-associated autoimmune diseases and fibrotic disorders such as SSc; in this context, the silica/RhoA/ROCK pathway may constitute a relevant therapeutic target.